Locke's Skeptical Realism - Conn, Christopher (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2022)
In this paper I contend that Locke is both a realist and a skeptic regarding the mind-independent bodies which are causally responsible for our ideas of sense. Although he frequently indicates that we have experiential knowledge of these bodies, I argue that this was not his considered position. In support of this conclusion I turn: first, to the basic contours of his accounts of knowledge and perception; second, to his argument for the existence of the material world; and third, to his discussions of judgment and probability. Locke’s considered position, I contend, is that instances of veridical perception do not yield genuine instances of knowledge. Rather, these perceptual encounters give rise to empirical judgments which enjoy a high degree of probability. While this prevents them from being suitable objects of knowledge, since Locke thinks that we can be nearly certain of their truth, he contends that we should not hesitate to think, speak and act as if they were instances of knowledge. I further argue that this account provides us with a more satisfying explanation of Locke’s dismissive attitude towards the skeptical hypotheses which appear throughout the Essay.